2023
DOI: 10.1007/s12144-022-04214-4
|View full text |Cite
|
Sign up to set email alerts
|

The influence of resilience on stress reaction of college students during COVID-19: the mediating role of coping style and positive adaptive response

Abstract: The COVID-19 pandemic was a stressful event for all. It threatened people’s physical and mental health. Previous studies have found that resilience can help people deal with stress and difficulties more effectively and prevent them from mental health problems. Coping style mediates the relationship between resilience and psychological well-being. Given the novelty and recency of the COVID-19, it is unknown whether resilience can also protect individuals in new difficulties, and whether the previous effective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…Moreover, physical activity can also reduce the level of cortisol, a stress hormone, and improve the immune system ( Gerber et al, 2020 ; Xu et al, 2021 ). Physical activity serves as a beneficial coping mechanism for negative emotions, especially during the quarantine period caused by the COVID-19 pandemic ( Xu and Yang, 2023 ). Some studies have demonstrated a negative correlation between moderate physical activity and negative emotions in college students ( Aperocho et al, 2021 ; Tao et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, physical activity can also reduce the level of cortisol, a stress hormone, and improve the immune system ( Gerber et al, 2020 ; Xu et al, 2021 ). Physical activity serves as a beneficial coping mechanism for negative emotions, especially during the quarantine period caused by the COVID-19 pandemic ( Xu and Yang, 2023 ). Some studies have demonstrated a negative correlation between moderate physical activity and negative emotions in college students ( Aperocho et al, 2021 ; Tao et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Psychological resilience has been found to predict the adoption of positive coping styles and inversely predict negative ones ( Blanco et al, 2008 ). Individuals exhibiting high psychological resilience tend to adopt positive coping styles and are more proactive in addressing and resolving negative emotions ( Gong et al, 2023 ; Xu and Yang, 2023 ). Therefore, the mechanism through which physical activity affects negative emotions may be attributed to the influence of psychological resilience and coping styles on college students’ negative emotions.…”
Section: Introductionmentioning
confidence: 99%
“…From this perspective, coping reflects the ability of an individual to relieve stress. As suggest by Agnew [ 42 ], stress is most likely to result in delinquency when “the constraints to delinquent coping are low and the constraints to nondelinquent coping are high, and the adolescent has a disposition for delinquent coping.” Coping is one of the critical mediating factors in the relationship between psychological stress and related consequences [ 43 ]. A large amount of empirical evidence also shows that adolescents’ responses to stress, including their coping styles, will lead to different consequences [ 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%